Modulación de genes endógenos relacionados al trofoectodermo mediante el sistema CRISPR/dCas9 en embriones bovinos - Alberio, Virgilia (2023)
Placental defects are common in bovine embryos produced by assisted reproductive techniques. In this species, most embryonic losses occur in the second week of\ngestation, when differentiation towards the first three lineages begins. Therefore, the regulation processes of cell fate, the embryo morphokinetic development and the\nmaintenance of genomic stability are critical elements in the acquisition of competence during development. The work carried out in this thesis aimed to induce trophectodermal cell differentiation in\nin vitro fertilized embryos, activating different genes and two different CRISPR/dCas9\nsystems. This strategy allows studying and understanding of the regulatory mechanisms\nthat occur during embryonic differentiation. It could also be used to remedy failures in the placental development of embryos produced by other reproductive biotechnologies.\nInitially, we sought to study the effect of simultaneous endogenous activation of TFAP2C and SMARCA4 genes using mRNA of the CRISPR/dCas9VP160 system. This was\nthought to direct the differentiation towards the trophectoderm in the early stages of bovine preimplantation embryos produced in vitro. In our hands, the microinjection of\nmRNA from the CRISPR/dCas9VP160 system was effective in modulating the\nsimultaneous induction of TFAP2C and SMARCA4 expression and genes downstream of these, with effective action more extended in time, compared to individual gene\nactivation. This effect also showed an increased number of trophectoderm cells, with a possible positive effect on the implantation rate and subsequent development of the\nembryos to term, if they were transferred.\nNext, we seek to analyze the activating effect of the CRISPR/dCas9p300 system on CDX2 and GATA3 in bovine embryos, to determine if it is a powerful model for use in the\nstudy of mechanisms related to lineage differentiation. The change in the activation\nsystem was aimed at going from CRISPR/dCas9VP160, whose main function is to recruit transcription factors, to CRISPR/dCas9p300 which acetylates promoter regions to activate genes, which is more powerful due to its direct action. In addition, since the\ntarget genes are expressed in more advanced stages of bovine preimplantation\ndevelopment, microinjection of circular DNA with the CRISPR/dCas9p300 system was performed, due to its greater stability. According to our results, a priori, the\nCRISPR/dCas9p300 system was not effective in modulating the endogenous expression of the CDX2 and GATA3 genes, due to the sequestration of the protein in the cytoplasm of the embryonic blastomeres.\nFinally, we sought to evaluate the effect of the endogenous activation of CDX2 and GATA3 in advanced stages of bovine preimplantation embryonic development, using\ncircular DNA of the CRISPR/dCas9VP160 system. With this new strategy, our results\ndemonstrated that using DNA from the CRISPR/dCas9VP160 system effectively\nmodulates the expression of the CDX2 and GATA3 genes, at least until day 4 of\nembryonic development. Activation of CDX2 gene expression induced the expression of genes upstream, related to the trophoblastic lineage, such as TFAP2C and SMARCA4,\nindicating a possible regulation associated with the trophoblastic lineage. In addition, GATA3 activation-induced gene expression from the trophectodermal lineage, such as CDX2. The dCas9VP160 protein was localized to the embryonic nucleus, as expected\nfor its function, although it did not affect the trophectoderm cell number.\nIn the three chapters of this thesis, the embryo quality parameters did not show\ndetrimental effects compared to the IVF control due to the microinjection technique itself or by introduction of the CRISPR/dCas9 system in the zygote. These results present the CRISPR/dCas9 system as a very useful strategy to correct\naberrant gene expression or to increase the number of trophectoderm cells of in vitroproduced embryos, thus impacting on the implantation rates and the production of\nhealthy offspring.